Arrogance in the Workplace: Implications for Mental Health Nurses. (3rd April 2015) - Cleary, Michelle; Walter, Garry; Sayers, Jan; Lopez, Violeta; Hungerford, Catherine
<x xml:space="preserve">Abstract</x> Cultures of performativity may contribute to organizational and individual arrogance. Workplace organizations have individuals who at various times will display arrogance, which may manifest in behaviours, such as an exaggerated sense of self-importance, dismissiveness of others, condescending behaviors and an impatient manner. Arrogance is not a flattering label and irrespective of the reason or the position of power, in the context of organizational behaviors, may not be useful and may even be detrimental to the work environment. Thus, it is timely to reflect on the implications of arrogance in the workplace. Advocacy and empowerment can be undermined and relationships adversely impacted, including the achievement of positive consumer outcomes. This paper provides an introduction to arrogance, and then discusses arrogance to promote awareness of the potential consequences of arrogance and its constituent behaviors.